2013 IEEE 17th International Conference on Intelligent Engineering Systems (INES) 2013
DOI: 10.1109/ines.2013.6632835
|View full text |Cite
|
Sign up to set email alerts
|

How to solve GNSS problem in critical environment?

Abstract: Information about user position is very important due to increasing interest in Location Based Services (LBSs). Nowadays, service providers try to provide ubiquitous LBSs. It leads to solve ubiquitous positioning, i.e. localize mobile user anywhere and anytime. This challenge mainly depends on the actual environment where user position is determined. The providers try to divide all environments to two basic types: outdoor and indoor. Positioning in both types requires different ways to estimate position. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Based on statistical outputs of measurements, carried out by the Police of the Slovak Republic in cooperation with the Regulatory Authority for Electronic Communications and Postal Services from 2012 to 2017, it was found that occurrence of the GNSS interference on GPS L1 frequency is mainly on highway sections, expressways and 1 st class roads, which are subject to a toll system that uses the GPS L1 [10]. Therefore, it is very important to analyse these types of roads and their parallelism with the approach axis for the LZZI 06 runway.…”
Section: Analysis Of Possible Locations For Detector Placementmentioning
confidence: 99%
“…Based on statistical outputs of measurements, carried out by the Police of the Slovak Republic in cooperation with the Regulatory Authority for Electronic Communications and Postal Services from 2012 to 2017, it was found that occurrence of the GNSS interference on GPS L1 frequency is mainly on highway sections, expressways and 1 st class roads, which are subject to a toll system that uses the GPS L1 [10]. Therefore, it is very important to analyse these types of roads and their parallelism with the approach axis for the LZZI 06 runway.…”
Section: Analysis Of Possible Locations For Detector Placementmentioning
confidence: 99%